55.8k views
2 votes
Math is not my favorite subject XD so help would be helpful

Math is not my favorite subject XD so help would be helpful-example-1

1 Answer

1 vote

Answer:

g(x) = g = 3(x)

g(-10) = -30

Explanation:

as we can see in the pattern, x times 3 is equal to g(x) -->

so we can conclude that g=3(x) which means g is 3 then multiply by x

finding g(-10) = 3(-10) => -30 and thus, we have our answers

Hope this helps ad sorry if it's a little not clear!

User Henrik Carlqvist
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.